Effect of Job Autonomy, Job Security and Employee Training on Perceived Organization Support - ALVI, Abdul Khaliq; HAIDER, Rizwan; ALI, Rana Raffaqat (Asian Journal of Empirical Research, 2013)
Perceived organizational support has been considered attention as main variable of research for long period. A number of studies have conducted on this variable. Due to its importance, latest researches are still considered as key variable. There is lack of researches about perceived organizational support in developing country like Pakistan. The main focus of this study is to explore the relationship of job autonomy, job security and employees training with perceived organizational support. Job autonomy, job security and employees training are considered as independent variables while perceived organizational support is taken as dependent variable. In this regard, current study has proposed three hypotheses about the positive relationship of these variables. This research has carried out on banking industry of Pakistan. For this purpose, sample of 312 respondents of city Lahore was selected randomly. For this purpose a structured questionnaire was designed for collection of primary data. Software, AMOS and SPPS were utilized for statistical analyses. Factor analysis, reliability analysis, regression analysis and correlation analysis were the test for conducting the current study. Results of this study have confirmed that job autonomy, job security and employees training are positively associated with perceived organizational support.